The use of, and controversy surrounding, the term atman in the Indian Buddhist tathagatagarbha literature. - Jones, CV (2015)
The tathāgatagarbha doctrine of Mahāyāna Buddhism affirms the existence of some permanent, significant content of sentient beings that is of the same character as a Buddha. While this alone was an important innovation within Buddhist thought, some of its authors ventured further to deem this significant content an ātman: a ‘self’, in apparent contradiction to the central Buddhist teaching of the absence of self (anātman) in the constitution of all beings.